Peran Pekerja Sosial dalam Mendukung Kebijakan Pengelolaan Sampah di Yogyakarta - Dian Pertiwi; Ramadhanita Mustika Sari (KOLONI, 2023)
The waste problem has negative impacts, such as declining human health quality, decreasing environmental quality and also having an impact on the socio-economic community. The solution can be done through policy making that is adjusted to the waste management law. This can be done with integrated cooperation between the government, the community and related private parties. Local governments also have the authority to make local regulations. This study aims to describe the role of social workers in supporting the success of waste management policies in Yogyakarta. This type of research is a literature study (library research). The results of this study show that there are three roles of social workers in supporting the success of waste management, namely by increasing social capital, working inside and outside the structure and creating social justice. The success of waste management policies can be achieved when there is integration between various functions in the system, including the implementation of social worker practices